2018
DOI: 10.1080/00365521.2018.1542455
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging and serology in the assessment of premalignant gastric pathology

Abstract: Background Patient outcomes in gastric adenocarcinoma are poor due to late diagnosis. Detecting and treating at the premalignant stage has the potential to improve this. H. pylori is also a strong risk factor for this disease. Aims Primary aims were to assess the diagnostic accuracy of magnified narrow band imaging (NBI-Z) endoscopy and serology in detecting normal mucosa, H. pylori gastritis and gastric atrophy. Secondary aims were to compare the diagnostic accuracies of two classification systems using both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
0
15
0
4
Order By: Relevance
“…The sensitivity and specificity of M-NBI images in the diagnosis of early gastric cancer were significantly higher than those of conventional white light images [13,27,32,33]. However, the non-experts often exhibited poor sensitivity and specificity in diagnosing early gastric cancer with M-NBI [14][15][16]. A potential solution to improve optical diagnosis is to apply CNN to M-NBI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity and specificity of M-NBI images in the diagnosis of early gastric cancer were significantly higher than those of conventional white light images [13,27,32,33]. However, the non-experts often exhibited poor sensitivity and specificity in diagnosing early gastric cancer with M-NBI [14][15][16]. A potential solution to improve optical diagnosis is to apply CNN to M-NBI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this algorithm, several studies have reported that the sensitivity of M-NBI in the diagnosis of early gastric cancer ranged from 85.7 to 97.3% and the specificity from 84.4 to 96.8% [11][12][13]. However, the diagnostic efficacy of non-experts in differentiating early gastric cancer from non-cancerous lesions by M-NBI was usually disappointing [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Application of the exclusion criteria to the identified papers found that three studies used magnified rather than standard endoscopy, 9,29,30 two studies included children, 11,31 two studies included an overlapping patient cohort, 20,22 one study did not include sufficient diagnostic data for calculation of performance characteristics 32 and one study was not performed at high resolution. 33 These studies are discussed further below but did not contain data for inclusion in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…За даними дослідників, загальноприйнята ендоскопія в цілому світі не дозволяє надійно діагностувати, тобто точно диференціювати і діагностувати передпухлинні стани шлунка (гелікобактерний гастрит, атрофію СО або КМ тощо). Застосування ендоскопів із високою роздільною здатністю (High resolution endoscopy), з режимами збільшення й вузькосмугової візуалізації («Narrow band imaging» -NBI) перевершує стандартну ендоскопію і дає можливість під час ендоскопічного дослідження вивчати мікроструктуру СО, виявляти дрібні вогнища КМ, дисплазії, атипії епітелію, які слабо візуалізуються при застосуванні звичайного освітлення, отримувати надточну, таргентну біопсію [1,[9][10][11][12][13][14][15][16].…”
Section: вступunclassified